Effects of the discharge of uranium mining effluents on the water quality of the reservoir: An integrative chemical and ecotoxicological assessment - Ferrari, Carla Rolim; Do Nascimento, Heliana De Azevedo Franco; Rodgher, Suzelei [UNESP]; Almeida, Tito; Bruschi, Armando Luiz; Nascimento, Marcos Roberto Lopes Do; Bonifácio, Rodrigo Leandro (Springer Nature, 2017)
The water quality of the Antas reservoir, under the influence of treated effluents from a uranium mining area Ore Treatment Unit (UTM) with acid mine drainage, was investigated. Samples were collected every 3 months from the Antas reservoir (CAB, P41-E and P14) and from the UTM (P41-S). Chemical and acute 48 h toxicity tests using Ceriodaphnia silvestrii and Daphnia magna analyses were carried out to determine the potential environmental risks due to discharging the uranium mine effluents into this reservoir. All the water samples taken from the treated effluent (P41-S) were positively correlated with elevated concentrations of uranium, manganese, aluminum, zinc and fluoride and with high electrical conductivity and pH values, being considered toxic. In November 2014 water samples taken from the reservoir showed chemical concentrations above the legislation limits for fluoride (4.5 mg L-1) uranium (0.082 mg L-1), sulfate (662.4 mg L-1), manganese (1.125 mg L-1) and aluminum (1.55 mg L-1), and in July 2015 for fluoride (2.55 mg L-1), uranium (0.01 mg L-1) and manganese (0.36 mg L-1). The extremely high average value for hardness (543.55 mg L-1) possibly reduced the toxicity potential of this chemical species mixture with respect to the bioindicators. The influence of the variation in water hardness on the toxicity of the cladocerans was discussed.